The Potential af Robusta Coffee Leaf Flour (Coffea canephora) as a Functional Food Ingredient: Antioxidant Activity Analysis - Parwati, Ni Komang; Rabani RS, I Gusti Agung Yogi; Widnyani, Ida Ayu Putu Ary; Putra, Anak Agung Ngurah Dwi Ariesta Wijaya; Sintyadewi, Putu Rima (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Functional food has become a rapidly growing segment in the global food industry, emphasizing the use of natural resources as sources of functional ingredients. One promising candidate for development is Robusta coffee leaf flour. The purpose of this study was to determine the optimal treatment and the effect of drying temperature on the antioxidant activity of Robusta coffee leaf flour. This study employed a one-factor randomized block design (RBD). The treatments consisted of combinations of temperature and time, with six levels: P1T1 = 50°C for 4 hours; P1T2 = 50°C for 5 hours; P1T3 = 50°C for 6 hours; P2T1 = 60°C for 4 hours; P2T2 = 60°C for 5 hours; and P2T3 = 60°C for 6 hours. Each treatment was repeated three times, resulting in a total of 18 experimental units. The data were analyzed using ANOVA and Duncan’s multiple range test for significant results. Findings indicated that the highest antioxidant activity was achieved at 60°C for 6 hours (P2T3), with a value of 73.51 ppm. Robusta coffee leaf flour demonstrates strong potential as a functional food ingredient, with optimal antioxidant activity achieved through specific drying conditions. Further research is recommended to investigate its bioactive compound profile and potential applications in food products.